The Association Between Combined Oral Contraceptive Use and the Incidence of High-Density Lesions on Digital Mammography - Carissa Faustina; Nina ISH Supit; Nungky Kusumaningtyas; Alvin Setiawan; Ratna Sari Wijaya (Medicinus, 2026)
Background: High mammographic density (MD) is an independent breast cancer risk factor that hinders early detection through the "masking effect." Global literature on the impact of combined oral contraceptives (COCs) remains inconsistent, with limited data available for the Indonesian population. This research aims to investigate the association between COC use and high-density lesions on digital mammography while evaluating the influence of family history.   Methods: This cross-sectional study analysed 158 subjects at Siloam MRCCC Hospital (Dec 2025–Jan 2026) using purposive sampling. Statistical associations were assessed using Chi-square and Fisher’s exact tests.   Result: Long-term COC use (≥5 years) was significantly associated with a reduced risk of high-density lesions (OR=0.28; 95% CI: 0.14–0.55; p<0.001) in perimenopausal women (median age 53). In contrast, family history was a potent risk factor, with a 100% prevalence of high-density lesions (p=0.003). After adjusting for family history, the protective association of COC use persisted (aOR=0.43). BMI and reproductive history showed no statistically significant associations.   Conclusion: Long-term COC use correlates with lower mammographic density in perimenopausal women, potentially mitigating diagnostic masking. However, family history remains a dominant factor that overrides these hormonal associations. These findings highlight the need for multifaceted screening strategies that integrate genetic predisposition and physiological tissue involution.